The metrical theorems on algebraic approximations in the field of power series - Sprindzuk, V. G. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Г. Спринджук. Метрические теоремы об алгебраических приближениях в поле степенных рядов V. Sprindžiuk. Algebrinių aproksimacijų laipsnių eilučių kūne metrinės teoremos